Use of space and home range characteristics of Lepilemur mittermeieri, an endangered sportive lemur endemic to the Ampasindava peninsula, north‐west Madagascar. Issue 8 (27th June 2019) - Wilmet, Leslie; Beudels‐Jamar, Roseline C.; Schwitzer, Christoph; Rakotondrainibe, Hajanirina; Devillers, Pierre; Vermeulen, Cédric
Abstract: Lepilemur mittermeieri, a little‐studied sportive lemur of north‐west Madagascar, endemic to the Ampasindava Peninsula, faces habitat loss through forest degradation and rapid fragmentation. Understanding its habitat requirement is the first step toward preservation of this threatened forest‐dependent species. In this study, we gathered data on the use of space and home range characteristics of L. mittermeieri . We studied individuals from early March to the end of June 2015 and 2016, in three sites of the Ampasindava peninsula. We radio‐tracked 15 individuals to obtain detailed information on the size and location of home ranges (around 450 hr of tracking). Direct observation and morphometric measurements provided additional data sets. Both kernel density estimation (KDE) and minimum convex polygon (MCP) methods yielded similar home range sizes (an average of 2.01 ha with KDE method and 1.96 ha with MCP method). We did not find differences in home range size between males and females, with respect to forest type or proximity to the forest edge. Home ranges overlapped and individuals showed low levels of territoriality. We highlighted a sexually‐dimorphic trait: males have longer upper canine than females. Our results constitute the first set of ecological information on Lepilemur mittermeieri and could be the basis for a conservation strategy for this endangered species with a very small distribution area. Abstract : Study sites on the Ampasindava peninsula Research Highlights: First research on the home range characteristics and habitat use of 15 Lepilemur mittermeieri (4 females and 11 males) in three forested areas of the Ampasindava Peninsula, north‐west Madagascar. Main findings from the study of habitat use of Lepilemur mittermeieri include: Home range averaged size of 2.01 ha (kernel density estimation method) No difference in home range size between males and females or proximity to the forest edge Overlapping home ranges and low levels of territoriality Morphometrics measured on 21 individuals: Sexual dimorphism: males have longer upper canine First data on habitat use and space requirements of Lepilemur mittermeieri provides essential information on some of the species basic needs. Such parameters are required for the evaluation of the species' conservation status. Lepilemur mittermeieri is mostly threatened by current and planned deforestation throughout the peninsula.